The Influence of Mentifact and Sociofact on The Design and Meaning of Rifa’iyah Batik Motifs for Wedding Ceremonies - Christine Claudia Lukman; Monica Hartanti (Wacana Seni Journal of Arts Discourse, 2025)
The Rifa’iyah community in Kalipucang Wetan Village, Batang Regency, follows the teachings of Kyai Haji (KH) Ahmad Rifa’iyah (1789–1871 CE). Before 1999, they lived in isolation due to accusations of heresy, requiring them to be entirely self-sufficient. This community adheres strictly to Rifa’i teachings in all aspects of life, including batik production. Their batik motifs reflect the Rifa’i prohibition against depicting living beings, such as animals. Women exclusively produce Rifa’iyah Batik, which holds significant cultural value in key life stages, including birth, marriage, and death. Traditionally, young women engaged in batik-making while awaiting marriage proposals and prepared multiple batik pieces for wedding ceremonies, including “seserahan” (dowry exchange) and “akad nikah” (marriage contract). This study examines the intersection of mentifact (Rifa’i teachings), sociofact (community customs), and artefact (Rifa’iyah Batik used in wedding rituals). Mentifacts represent a culture’s ideology, values, and beliefs, while sociofacts refer to the social structures and customs shaping behaviour. In this context, artefacts are human-made objects that address practical and symbolic needs. This study employs a qualitative descriptive approach to gather data through observations, interviews with batik artisans and experts, and a literature review. It uses social semiotics to interpret Rifa’iyah wedding batik as a text composed of signs whose meanings are shaped by the community’s social codes. The findings reveal that artefacts and sociofacts within the Rifa’iyah community influence the visual elements and meanings of batik, emphasising values of loyalty, unity, sincerity, and resilience in marriage.